Platelet Glycoprotein Ia* Is the Processed Form of Multimerin – Isolation and Determination of N-terminal Sequences of Stored and Released Forms - Polgár, János; Magnenat, Edith; Wells, Timothy N. C.; Clemetson, Kenneth J. (Thrombosis and Haemostasis, 1998)
Glycoprotein Ia* (GPIa*), a very high molecular mass, platelet α-granule protein consisting of 167 kDa subunits disulphide-linked in a multimeric structure, was first described by Bienz and Clemetson in 1989 (J. Biol. Chem. 264, 507-514). In 1991 Hayward et al. (J. Biol. Chem. 266, 7114-7120) independently identified a platelet protein with multimeric structure. Despite strong similarities to GPIa* they concluded that it was a novel multimeric protein and named it first p-155 and later, multimerin. Multimerin has also been found in endothelial cells and has been cloned recently from an endothelial cell cDNA library. This has made it possible for us to clarify the relationship between GPIa* and multimerin. GPIa* was isolated from platelet releasate and the N-terminal sequence of 167 kDa and 155 kDa subunit species were determined. The N-terminal 15 amino acids of GPIa* were identical to the deduced amino acids 184-198 of endothelial multimerin. The N-terminal sequence of the 155 kDa protein was identical to the deduced amino acids 318-326 of multimerin. Thus, platelet GPIa* (167 kDa) is the main processed form of multimerin stored in platelet α-granules. The GPIa*/processed multimerin (167 kDa) still contains an RGDS sequence near its N-terminus as well as an EGF domain which may be involved in binding to the platelet surface after release. This sequence and domain are cleaved off in the p-155 form, described earlier as platelet multimerin, which is probably formed after release from α-granules.